Rekonstruksi Pemikiran Teologi Islam Moderat dalam Menghadapi Tantangan Radikalisme Kontemporer - Ahmad Fauzi; Siti Rahmawati; Muhammad Ridwan (Al-Jinan : Jurnal Studi Islam, 2026)
This study examines the reconstruction of moderate Islamic theological thought as a counter-narrative framework against contemporary radicalism in Indonesia. The background lies in the persistent challenge of extremist ideologies that exploit theological texts to justify violence and exclusivism, threatening the fabric of the nation's religious pluralism. The purpose is to analyze the doctrinal foundations and methodological approaches of moderate Islamic theology and to formulate a reconstructive framework applicable to contemporary deradicalization efforts. Using a qualitative approach with library research and hermeneutical analysis methods, this study examines classical and contemporary Islamic texts, fatwas, and scholarly works on wasatiyyah Islam. Findings reveal that moderate Islamic theology, rooted in the principles of tawassut, tawazun, and tasamuh, provides robust theological arguments against radical interpretations and offers an inclusive vision of Islamic civilizational contribution. The study concludes that systematic reconstruction of moderate Islamic theology through educational institutions and scholarly discourse is essential for sustainable deradicalization in Indonesia